(3GdOQ GdfVjO aj TQM GdbUjO (B( (3GdTGWHjI (B)s - (3TeS GdOjf eMeO Hf CMeO Hf YeGQI GdZSGfi GdCfOdSjs; (3GdbGSe Hf ajQg Hf Nda Hf CMeO GdQYjfj, CHh eMeO GdTGWHj,J (B590 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HLdGd YXeJg GdeJbOS Yf GdCTHGg HceGd QHhHjJg s
(3BNQgG (B:s
(3GdRQfH TLQ cHjQ QGFMJg cQGFMI GdCJQL hRfg aYdd , eKd LYaQ haYdd ai GdcdGe cKjQ hGddg CYde Je GdcJGH Hef Gddg hdWag s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B110s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdbQGAGJ hGdJLhjOs